ANALISIS PEMODELAN PRILAKU STABILITAS LERENG DENGAN MENGGUNAKAN APLIKASI GEOSLOPE - Nofrizal, Nofrizal; Farhan, Muhammad (ITP Press, 2024)
Sitinjau Laut is an area of ​​Bukit Barisan rock which is dominated by the weathering of volcanic rocks in the form of clay, sandy clay with pebble-sized rocks to large chunks of clay and sandy clay which are very plastic, if exposed to water on the cliffs it will easily trigger ground movement (Ade Edwar, 2022). In 2019, natural disasters frequently occurred on the Sitinjau Laut km 23 road section. Landslides occurred due to high rainfall and steep cliff structures and made the road impassable (DIBI, 2019). The Sitinjau Laut road is an important means of transportation in the city of Padang. The impact of the landslide that occurred on the Sitinjau Laut road section resulted in disruption of traffic flow on the road. The aim of this research is to determine the value of the safety factor (Factor of Safety) of the slope of the research location using the Geo - Slope/W 2012 program. W 2012 is 0.581. From the results obtained it can be said that the slopes of the research area are unsafe because the Factor of Safety (FoS) value is less than 1. Simulations using several angle variations of 30 ̊, 45 ̊, 60 ̊ and 90 ̊ obtained the minimum and maximum Factor of Safety (FoS) values.) is less than 1. Thus, slope stability using several angle variations is unsafe.